2018
DOI: 10.1159/000495822
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Laminin (LN)- α5 is Associated with Preeclampsia and Impairs Trophoblast Cell Viability and Invasiveness Through PI3K Signaling Pathway

Abstract: Background/Aims: Preeclampsia (PE) is a gestational disorder defined as hypertension and proteinuria, which is deemed a major cause of maternal and neonatal mortality and morbidity worldwide. The aim of this study was to investigate the expression patterns of placental laminin (LN)-α5 expression in normal and PE pregnancies, as well as evaluating the effects of LN-α5 on trophoblast proliferation, apoptosis, and invasion. Methods: LN-α5 expression levels were examined by reverse-transcriptase polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…These contradictory findings have suggested that autophagy activity in trophoblasts might change at different stages of pathogenesis. The Akt/mTOR signaling pathway is critical for cell autophagy and several groups reported that suppression of this pathway contributes to increasing autophagy and cell apoptosis in trophoblasts (Yeh et al 2016, Zhang et al 2018, Chen et al 2019. Here, our results revealed that DCN promotes autophagy in HTR-8 cells, in accordance with previous findings that DCN is an autophagy inducer in endothelial cells (Buraschi et al 2013) and breast carcinoma cells (Neill et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…These contradictory findings have suggested that autophagy activity in trophoblasts might change at different stages of pathogenesis. The Akt/mTOR signaling pathway is critical for cell autophagy and several groups reported that suppression of this pathway contributes to increasing autophagy and cell apoptosis in trophoblasts (Yeh et al 2016, Zhang et al 2018, Chen et al 2019. Here, our results revealed that DCN promotes autophagy in HTR-8 cells, in accordance with previous findings that DCN is an autophagy inducer in endothelial cells (Buraschi et al 2013) and breast carcinoma cells (Neill et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In particular, laminin LAMA1 was highly expressed in the first trimester, whereas LAMB3, LAMA2, LAMC3 were upregulated in the second trimester. Laminins have an important role during implantation ( Haouzi et al, 2011 ), maintenance of trophoblast stemness ( Kiyozumi et al, 2020 ) and EVT migration ( Zhang et al, 2018b ).…”
Section: Resultsmentioning
confidence: 99%
“…Downregulation of receptor tyrosine kinase-like orphan receptor 1 (ROR1) in PE placenta inhibits human trophoblast cell proliferation, migration, and invasion via regulating the PI3K/ Akt/mTOR pathway [24]. Laminin (LN)-α5 downregulation is associated with PE placenta and impairs trophoblast cell viability and invasiveness through the PI3K/Akt/mTOR pathway, which could be a causative factor of PE pathogenesis [33]. Concerning the mechanism of the DDX46 function, we further discovered that knockdown of DDX46 caused significantly decrease in the expression levels of p-Akt and p-mTOR in trophoblast cells.…”
Section: Discussionmentioning
confidence: 99%